Alcohol consumption and mortality in patients undergoing coronary artery bypass graft (CABG)-a register-based cohort study. Issue 1 (December 2016) - Grabas, Mads; Hansen, Steen; Torp-Pedersen, Christian; Bøggild, Henrik; Ullits, Line; Deding, Ulrik; Nielsen, Berit; Jensen, Per; Overgaard, Charlotte
Abstract Background Previous studies have shown that compared with abstinence and heavy drinking, moderate alcohol consumption is associated with a reduced risk of mortality among the general population and patients with heart failure and myocardial infarction. We examined the association between alcohol consumption and mortality in coronary artery bypass graft (CABG) patients. Method We studied 1, 919 first-time CABG patients using data on alcohol consumption and mortality obtained from Danish national registers from March 2006 to October 2011. Alcohol consumption was divided into the following groups: abstainers (0 units/week), moderate consumers (1–14 units/week), moderate-heavy drinkers (15–21 units/week) and heavy drinkers (>21 units/week). Hazard ratios (HR) of all-cause mortality were calculated using Cox proportional hazard regression analysis. Results The median follow-up was 2.2 years [IQR 2.0]. There were 112 deaths, of which 96 (86 %) were classified as cardiovascular. Adjustments for age and sex showed no increased risk of all-cause mortality for the abstainers (HR 1.61, 95 % CI, 1.00–2.58) and moderate-heavy drinkers (HR 1.40, 95 % CI, 0.73–2.67) compared with moderate consumers. However, heavy drinkers had a high risk of all-cause mortality compared with moderate consumers (HR 2.44, 95 % CI, 1.47–4.04). A full adjustment showed no increase in mortality for the abstainers (HR 1.59, 95 % CI, 0.98–2.57) and moderate-heavy drinkers (HR 1.68, 95 % CI, 0.86–3.29), while heavy drinkers were associated with an increased mortality rate (HR 1.88, 95 % CI, 1.10–3.21). There was no increased risk of 30-day mortality for the abstainers (HR 0.74, 95 % CI, 0.23–2.32), moderate-heavy drinkers (HR 0.36, 95 % CI, 0.07–1.93) and heavy drinkers (HR 2.20, 95 % CI, 0.65–7.36). Conclusion There was no increased risk of mortality for abstainers (0 units/week) or moderate-heavy drinkers (15–21 units/week) following a CABG. Only heavy drinking (>21 units/week) were significantly associated with an increased mortality rate. These results suggest that only heavy drinking present a risk factor among CABG patients.